The Mutation of the rpoS Gene, the Central Regulator of Stationary Phase, Affects the Cell Division in Flexibacter chinensis (Journal of Sciences, Islamic Republic of Iran)
A one kb portion of the rpoS gene from Flexibacter chinensis was isolated by PCR, sequenced and compared to the rpoS gene of a variety of other organisms. The gene was found to be 98% similar to previously sequenced genes. Mutation of the rpoS gene with tri-parental mating produced strain JR101 and the growth rate of the mutant was compared with that of the wild-type. The mutant grew slower, and produced longer cells in the stationary phase. The cell size of the mutant was not reduced during the stationary phase, suggesting that cell division was inhibited during the stationary phase. The mutant also showed a much reduced survival under starvation conditions compared to the wild-type strain.